Metal-like fluorine-doped β-FeOOH nanorods grown on carbon cloth for scalable high-performance supercapacitors. (January 2015) - Chen, Li-Feng; Yu, Zi-You; Wang, Jia-Jun; Li, Qun-Xiang; Tan, Zi-Qi; Zhu, Yan-Wu; Yu, Shu-Hong
Abstract: At present, supercapacitors employed in the market have been growing rapidly, including portable electronics, hybrid electric vehicles, and industrial electric systems. Nevertheless, there are some limitations in supercapacitor devices, such as low energy density and high production cost, which are recognized as the major challenges for their developments. The performance of these devices depends intimately on the properties of electrode materials, therefore one of the most intensive approaches is to design novel electrode materials. Herein, a new scalable electrode material, metal-like fluorine-doped β -FeOOH nanorods grown on carbon cloth has been engineered for enhancing the energy density meanwhile retaining the high power density of the supercapacitor via an easy, low-cost, and large-scale fabrication approach. The optimal supercapacitor device exhibits a high-class supercapacitor performance with a good rate capability, high energy density (1.85 mW h cm −3 ), large power density (11.11 W cm −3 ), and long cycle span (no decrease of capacitance after 5000 cycles). Moreover, this kind of material represents an alternative promising candidate for large-scale and high-performance energy storage devices. Graphical abstract: Highlights: A novel scalable electrode material, metal-like β -FeO(OH, F) nanorods grown on carbon cloth has been successfully engineered for improving the energy density meanwhile retaining the high power density of supercapacitors. Density functional theory (DFT) calculations are performed to explore the reason why the as-prepared electrode material presents a good rate retention. The optimal supercapacitor device exhibits a good rate capability, high energy density of 1.85 mW h cm −3, maximum power density of 11.11 W cm −3, and long cycle span. This research paves an efficient and promising way for developing the low-cost, scale-up, and high-performance electrode material of energy storage devices.